Skills supply and demand in Europe : methodological framework - (:unkn) unknown (Publications Office of the European Union, 2012)
"This publication provides an overview of the methodology underpinning the Cedefop skills supply and demand forecast. The aim is to share the knowledge acquired during the development of the different systems, modules and models and to highlight the results, which have already aroused considerable interest. Cedefop's forecast is not intended to replace forecasting efforts in individual countries, but to share the knowledge acquired during the development of different systems and methods. This shared knowledge can help to improve the methods used in each country and to resolve outstanding issues. Cedefop's forecast can also inspire new forecasting initiatives. The feedback provided by countries can in turn help make the European forecast even more precise." (Hrsg., BIBB-Doku)
Keywords: G 1.2.3.2 Anforderungen & Bedarfe; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; I 2.2 Europa; Früherkennung; Qualifikationsbedarf; Qualifikationsnachfrage; Beschäftigungsentwicklung; Prognose; Methodik; Europa